2020
DOI: 10.1016/j.ygyno.2019.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery versus laparotomy for radical hysterectomy in the management of early-stage cervical cancer: Survival outcomes

Abstract: Objective: To compare oncologic and perioperative outcomes in patients who underwent minimally invasive surgery (MIS) compared to laparotomy for newly diagnosed early-stage cervical carcinoma. Methods:We retrospectively identified patients who underwent radical hysterectomy for stage IA1 with lymphovascular invasion (LVI), IA2, or IB1 cervical carcinoma at our institution from 1/2007-12/2017. Clinicopathologic characteristics and surgical and oncologic survival outcomes were compared using appropriate statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 41 publications
3
72
0
1
Order By: Relevance
“…The KGOG 1028 study 19 also showed that for patients with tumors <2 cm, laparoscopic surgery had worse DFS than laparotomy, but there was no difference in OS. Similarly, Alexander et al 14 also reported similar results as described above, which published 20 Notably, in that study, the minimally invasive group had a larger proportion of residual lesions, and a lower proportion of postoperative risk factors. Under this uneven risk factors, it seems that further evidence is needed to conclude that minimally invasive surgery did not bring worse prognosis.…”
Section: Discussionsupporting
confidence: 75%
“…The KGOG 1028 study 19 also showed that for patients with tumors <2 cm, laparoscopic surgery had worse DFS than laparotomy, but there was no difference in OS. Similarly, Alexander et al 14 also reported similar results as described above, which published 20 Notably, in that study, the minimally invasive group had a larger proportion of residual lesions, and a lower proportion of postoperative risk factors. Under this uneven risk factors, it seems that further evidence is needed to conclude that minimally invasive surgery did not bring worse prognosis.…”
Section: Discussionsupporting
confidence: 75%
“…Laparoscopic radical hysterectomy (LRH) was shown to have more favorable short-term outcomes than open surgery, including less blood loss, lower transfusion rates, shorter operative times and hospital stays, and fewer postoperative complications ( 10 14 ). Several retrospective studies also showed that LRH and ARH have equivalent progression-free survival (PFS) and overall survival (OS) rates ( 11 , 15 , 16 ). LRH has been gradually accepted as a reasonable alternative to ARH for patients with early-stage cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This was mainly out of fear and concerns that Minimally Invasive Surgery (MIS) was associated with poorer disease-free survival and overall survival based on the LACC trial [2]. This is in contrast to many other centres who have compared their data to those of the LACC trial and findings were inconsistent [4][5][6][7][8]. Particularly, studies have found that with appropriate patient selection, Laparoscopic Radical Hysterectomy is safe for the management of Early Stage Cervical Cancer with small tumors that are 2 cm or less in size [9].…”
Section: Real-world Impact So Farmentioning
confidence: 99%